2015
DOI: 10.1007/s13277-015-3200-1
|View full text |Cite
|
Sign up to set email alerts
|

Association of microRNA 17–92 cluster host gene (MIR17HG) polymorphisms with breast cancer

Abstract: Breast cancer incidence and mortality rates are increasing despite our current knowledge on the disease. Ninety-five percent of breast cancer cases correspond to sporadic forms of the disease and are believed to involve an interaction between environmental and genetic determinants. The microRNA 17-92 cluster host gene (MIR17HG) has been shown to regulate expression of genes involved in breast cancer development and progression. Study of single-nucleotide polymorphisms (SNPs) located in this cluster gene could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 38 publications
1
31
0
Order By: Relevance
“…It has been reported that the SNP rs9515692 in the promoter region of miR‐17‐92 was a protective factor for the susceptibility of systemic lupus erythematosus (Wang et al, ). Statistical analysis of allele frequencies in cases and controls in the Genomics Research Centre Breast Cancer population for rs7336610 showed significance; and haplotypic analysis of results showed that the AC haplotype of rs4824505/rs7336610 are associated with risk of breast cancer development (Chacon‐Cortes, Smith, Lea, Youl, & Griffiths, ). In this study, we investigated the association between the polymorphisms of MIR17HG and colorectal cancer risk in the Chinese Han population.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the SNP rs9515692 in the promoter region of miR‐17‐92 was a protective factor for the susceptibility of systemic lupus erythematosus (Wang et al, ). Statistical analysis of allele frequencies in cases and controls in the Genomics Research Centre Breast Cancer population for rs7336610 showed significance; and haplotypic analysis of results showed that the AC haplotype of rs4824505/rs7336610 are associated with risk of breast cancer development (Chacon‐Cortes, Smith, Lea, Youl, & Griffiths, ). In this study, we investigated the association between the polymorphisms of MIR17HG and colorectal cancer risk in the Chinese Han population.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, we found that rs17735387 was related to the improved prognosis of glioma patients, particularly in low-grade glioma. Previously, rs7336610 was reported to be related to the risk of multiple myeloma and breast cancer, and rs17735387 not share any relationship with multiple myeloma risk and prognosis [14,22]. These results suggested that MIR17HG polymorphisms might have a different effect on the occurrence of different cancer types.…”
Section: Discussionmentioning
confidence: 89%
“…Research has shown that lncRNA MIR17HG was overexpressed in glioma and lncRNA MIR17HG knockdown inhibited glioma proliferation, migration, and invasion, suggesting lncRNA MIR17HG might facilitate glioma malignant progress [12]. Recent increasing evidence has indicated that the genetic polymorphisms of MIR17HG was associated with the occurrence of multiple tumors, such as lymphoma, colorectal cancer, breast cancer [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have confirmed that it participates in various growth and development processes such as cell proliferation and differentiation, angiogenesis, and plays an important role [10][11][12]. More and more studies have shown that the polymorphism of MIR17HG gene was associated with breast cancer [13], colorectal cancer [14], Multiple Myeloma [15].…”
Section: Introductionmentioning
confidence: 94%